Temporal Expression Patterns of Clock Genes and Aquaporin 5/Anoctamin 1 in Rat Submandibular Gland Cells - Satou, Ryouichi; Sato, Masaki; Kimura, Maki; Ishizuka, Yoichi; Tazaki, Masakazu; Sugihara, Naoki; Shibukawa, Yoshiyuki (Frontiers in Physiology, 2017)
Circadian rhythms are essential for health and regulate various physiological functions. These rhythms are regulated by a negative-feedback loop involving clock genes in the suprachiasmatic nucleus (SCN) and peripheral tissues. The rate of secretion of salivary substances, ions, and water follows a circadian rhythm, however, the relationship between the molecular mechanism of salivary secretion and peripheral circadian rhythm is not yet clear. Anoctamin 1 (ANO1, also known as TMEM16A) and Aquaporin 5 (AQP5) play an important role in the transport of ions and water in the submandibular glands (SGs). We examined the interaction between the rhythmic expression pattern of the clock genes, Ano1 and Aqp5, in rat whole SGs as well as isolated acinar and ductal cells. Circadian rhythmic expression for Bmal1, Per1, Per2, Clock, Cry1, Cry2, Rorα and Rev-erbα mRNAs, also called the clock genes, was observed in rat SGs by semi-quantitative RT-PCR analysis. We also observed rhythmic patterns in Ano1 and Aqp5 mRNA expression. The expression of ANO1 protein also showed circadian rhythm, as confirmed by western blot analysis. We could not observe any time delay between the peak expression of ANO1 protein and its mRNA. Expression levels of the clock gene mRNAs in the ductal cells was higher than that in acinar cells, however, rhythmic oscillations were observed in both. Our results suggest that SGs have peripheral clocks, and rhythmic expressions of Ano1 and Aqp5 along with the clock genes, may play an important role in the circadian regulation of salivary secretion.